Genotypic Characterization of Mycobacterium bovis Isolates From Dairy Cattle Diagnosed With Clinical Tuberculosis - de Melo, Elizabeth Hortêncio; Gomes, Harrison Magdinier; Suffys, Philip Noel; Lopes, Márcia Quinhones Pires; de Figueiredo Teixeira, Raquel Lima; dos Santos, Ícaro Rodrigues; Franco, Marília Masello Junqueira; Langoni, Helio; Paes, Antonio Carlos; Afonso, José Augusto Bastos; de Mendonça, Carla Lopes (Frontiers in Veterinary Science, 2021)
Molecular diagnosis of bovine tuberculosis plays an essential role in the epidemiological knowledge of the disease. Bovine tuberculosis caused by Mycobacterium bovis represents a risk to human health. This study aimed to perform the genotypic characterization of M. bovis isolated from bovines diagnosed as tuberculosis from dairy herds in the state of Pernambuco, Brazil. Granulomas from 30 bovines were sent for microbiological culture and colonies compatible with Mycobacterium spp were obtained in at least one culture from 17/30 granulomas. All isolates were confirmed to be M. bovis by spoligotyping and 24loci MIRU-VNTR typing. While spoligotyping characterized the isolates as SB0121, SB0295, SB0852, SB0120 and an unclassified genotype, 24loci MIRU-VNTR rendered two clusters of two isolates each and 13 unique profiles. Loci ETR-A showed higher discriminatory power, and loci (ETR-B, ETR-C, MIRU16, MIRU27 and QUB26) showed moderate allelic diversity. This is the first study on genetic variability of the infectious agent cause of bovine TB in Pernambuco and demonstrates variability of strains in the state. Thus, it corroborates the importance of this microorganism as agent of bovine tuberculosis and its zoonotic potential, being this epidemiological tool determinant in the rigor of the sanitary practices of disease control in dairy herds.